①(1/2√3+√8)(√8-1/2√3) ②(10√48-6√27+4√12)÷√6③(√2-√12)(√18+√48)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/01 17:51:50
①(1/2√3+√8)(√8-1/2√3)②(10√48-6√27+4√12)÷√6③(√2-√12)(√18+√48)①(1/2√3+√8)(√8-1/2√3)②(10√48-6√27+4√12)÷
①(1/2√3+√8)(√8-1/2√3) ②(10√48-6√27+4√12)÷√6③(√2-√12)(√18+√48)
①(1/2√3+√8)(√8-1/2√3) ②(10√48-6√27+4√12)÷√6
③(√2-√12)(√18+√48)
①(1/2√3+√8)(√8-1/2√3) ②(10√48-6√27+4√12)÷√6③(√2-√12)(√18+√48)
①原式=(√8)²-(1/2√3)²=8-1/12=95/12
②原式=(40√3-18√3+8√3)÷(√6)=(30√3)×(√6/6)=15√2
③原式=(√2-2√3)(3√2+4√3)=6+4√6-6√6-24=-2√6-18
2/3√2-√1/2+√8-√3+√12-√18
①(√3+√2)+(√3-√2)/(√3+√2)-(√3-√2)②x^2-x-3=0③√18-2/√2-√8/2+(√5-1)^0
①(1/2√3+√8)(√8-1/2√3) ②(10√48-6√27+4√12)÷√6③(√2-√12)(√18+√48)
1 √32-3√1/2+√22 √12+√27/√3-√1/3×√123 √50+√30/√8-44 √24+√216/√6+55 (√6-2√15)×√3-6√1/26 √2/3-4√216+43√1/67 √8+√30-√28 √1/7+√63-√1129 √40-5√1/10+√1010 √2+√8/√2
计算:①(√5-1)^2+(4/√5-1)②(√2+√3+√6)×(√2-√3+√6)③√27-(√1/3)=________④(√8又1/3)-(√3/8)-√54+(√1/3)=________⑤√3+√12-3√18+7√2⑥√48-1/3+√0.75⑦√75-(1/√3-√2)+
化简1/1+√2+1/√2+√3+...+1/√8+√9
1/2√24-6√8/3+√3(√3-√2)
化简:2√8+√1(√27+√3)分之√3 - 2
(√12-√4/3)-2(√1/8-1/√2-√18)
[√12-√(4/3)]-2[√(1/8)-1/√2-√18]
4√6-4√1/2+3√8
√1/5=(),计算:√2/3-√3/2,√18-√8+√1/8,√25/2+√99-√18
化简:√18-√8;(√3+1)²计算:(√2+1)(√2-1);√16+√0.25-³√27;√20+√5-2√5;√12+√48-3√1/3
(√24-√0.5-3√2/3)-(√1/8-√6)
√48÷√3+√32-5×√1/2+6√1/8等于?
(√0.5-2√1/3+√32)-(√75+√1/8)拜托各位大神
(√12-√0.5-2√1/3)-(√1/8-√18)
√0.5+√32-2√1/3-√1/8-√75